2018
DOI: 10.1111/1753-6405.12806
|View full text |Cite
|
Sign up to set email alerts
|

Keratinocyte cancers in South Australia: incidence, geographical variability and service trends

Abstract: Objectives: To determine the incidence, multiplicity, geographical variability and service trends of keratinocyte cancers (KC) in South Australia (SA). Methods:Medicare Australia data with a unique identifier were used to assess the number of people treated over years [2010][2011][2012][2013][2014]. A maximum of one KC service claim per year was used to determine incidence. Age-standardised rates were estimated as were KC service activity trends.Results: There were 497,581 services to 204,183 SA residents for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 24 publications
(40 reference statements)
3
15
0
Order By: Relevance
“…After analyzing ASIR of NMSC in our study, noticeable differences between gender were found: they were much higher in men than in women during the whole study period (1999-2015). Our results are compatible with findings from studies in other countries (4,33,34,35). Incidence rates tend to be higher in men than in women most likely because in Serbia, men are more likely to have an outdoor occupation.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…After analyzing ASIR of NMSC in our study, noticeable differences between gender were found: they were much higher in men than in women during the whole study period (1999-2015). Our results are compatible with findings from studies in other countries (4,33,34,35). Incidence rates tend to be higher in men than in women most likely because in Serbia, men are more likely to have an outdoor occupation.…”
Section: Discussionsupporting
confidence: 93%
“…Our study showed that NMSC is the most common among the elderly; the age-specific incidence rates is the highest in the age group over 70 years (50%) and very low in the younger age (3%). The age distribution of NMSC cases is similar to other reports (4,25,26,27,28). Many studies have confirmed that cumulative exposure to UVR, especially in the first two decades of life, plays the key role in carcinogenic process of skin cancer (7,8).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…39 For skin cancer, MBS data captures all but 1.6% of procedures and prevalence estimates from these data have been shown to differ from other sources for those aged ≥80 years. 32 To address this limitation, individuals who received health care services under the Department of Veteran's Affairs program were excluded from the study. 40 Additionally, the aged care eligibility assessment used to ascertain the history of skin cancer and cataract only records up to 10 health conditions; the aged care eligibility assessors only report those conditions that have been diagnosed by a suitably qualified individual and impact on the person's need for assistance.…”
Section: Discussionmentioning
confidence: 99%